INFORMATION AND MILITARY SECURITY AS AN ELEMENT OF NATIONAL SECURITY OF UKRAINE - Artemov , Volodymyr; Khoroshko, Volodymyr; Khokhlacheva, Yuliya; Pogorelov, Volodymyr (Ukrainian Information Security Research Journal, 2022)
National security is an important component of a sovereign geopolitical unit. For Ukraine, as a state that has gained independence relatively recently, it is important to ensure its own sovereignty in all spheres. In today's world, the information space plays a major role as a database and a source of military-strategic information. The sources themselves are divided into three groups according to their influence.It is especially important to ensure the functioning system of information and military security of Ukraine. This list includes not only foreign policy information, but also all areas that ensure the full functioning of the state.In addition to the protection of one's own information space, the goal is military opposition to the aggressor, where the experience is already quite extensive. In the information war with Russia, a significant point is the informational and psychological influence in relation to various segments of the population. At the moment, the war in the information space has acquired a hybrid character and is expressed in the implementation of information technologies in practice.The emphasis of the military struggle is shifting towards